Crucial accountability : tools for resolving violated expectations, broken commitments, and bad behavior - Patterson, Kerry, 1946-; Grenny, Joseph; Maxfield, David G., 1954-; McMillan, Ron; Switzler, Al (McGraw Hill-Ascent Audio, 2014)
Hold anyone accountable. Master performance discussions. Get RESULTS. Behind the problems that routinely plague our organizations and families, you'll find individuals who are either unwilling or unable to deal with broken promises. Colleagues break a rule, coworkers miss a deadline, friends fail to live up to commitments (or just plain behave badly), and nobody says a word. Nobody holds anyone accountable. With repeated infractions, individuals become increasingly upset until they finally do speak their minds, but they do so poorly--often creating whole new sets of problems. Research proves that mishandled disappointments aren't just morale killers, they're institution killers--diminishing organizational performance by 20 to 50 percent and accounting for up to 90 percent of all divorces. Drawing from 10,000 hours of observations, Crucial Accountability teaches you how to deal with common infractions such as: An employee speaks to you in an insulting tone that crosses the line between sarcasm and insubordination. Now what? Your boss just demanded that you meet a deadline you know you can't meet--and he clearly doesn't want to hear complaints about it. Your son walks through the door sporting colorful new body art that raises your blood pressure by 40 points. Speak now or pay later. Family members fret over how to tell Granddad that he should no longer drive his car. This is going to get ugly. A nurse worries about what to say to an abusive physician. She quickly remembers "how things work around here" and decides not to say anything. Everyone knows how to run for cover, or, if sufficiently provoked, step up to problems in a way that causes a real ruckus. Crucial Accountability teaches you how to deal with violated expectations in a way that solves the problem at hand without harming the relationship--and, in fact, even strengthens it. Broken promises, missed deadlines, poor behavior--they don't just make others' lives miserable; they can sap up to 50 percent of organizational performance and account for the vast majority of divorces. Crucial Accountability offers the tools for improving relationships in the workplace and in life and for resolving all these problems--permanently. PRAISE FOR CRUCIAL ACCOUNTABILITY: "Revolutionary ideas ... opportunities for breakthrough ..."--Stephen R. Covey, author of The 7 Habits of Highly Effective People "Unleash the true potential of a relationship or organization and move it to the next level." -- Ken Blanchard, coauthor of The One Minute Manager "The most recommended and most effective resource in my library." -- Stacey Allerton Firth, Vice President, Human Resources, Ford of Canada "Brilliant strategies for those difficult discussions at home and in the workplace." -- Soledad O'Brien, CNN news anchor and producer "This book is the real deal ... Read it, underline it, learn from it. It's a gem." -- Mike Murray, VP Human Resources and Administration (retired), Microsoft